2011
DOI: 10.1007/s12303-011-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Çamardı Formation sediments, central Anatolia (Turkey): implication of source area weathering, provenance, and tectonic setting

Abstract: The upper Cretaceous-Eocene Çamardl Formation is exposed along the northern edge of the Ulukl la Basin (central Anatolia) and consists of turbiditic sediments. The sediment geochemistry has been studied in order to understand the provenance, source area weathering, and tectonic setting of the basin. Çamardl Formation sediments are characterized by low to moderate SiO 2 contents, variable abundances of major elements, and a relatively high proportion of ferromagnesian elements. Evidence from discrimination diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 32 publications
2
14
0
2
Order By: Relevance
“…The ratio of SiO2/Al2O3 (5.7-7.4) of the studied sediments was higher than the equivalent ratio for both UCC and PAAS (Table 1), reflecting that the Brahmaputra sediments were derived largely from crustal felsic sources. Moreover, the Al2O3/TiO2 ratio, which can be used to infer mafic, intermediate and felsic rock compositions (see Keskin [40] and references therein) varied from 10 to 34 and according to Hayashi et al [41] the Al2O3/TiO2 ratios in mafic rock types range from ~3 to 8, intermediate types from ~8 to 21, and felsic types from ~21 to 70. The high Al2O3/TiO2 values in the Brahmaputra sediments (average of ~8) combined with high SiO2 contents (up to 76 wt.%) indicate derivation from mostly intermediate to felsic rock sources.…”
Section: Major Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of SiO2/Al2O3 (5.7-7.4) of the studied sediments was higher than the equivalent ratio for both UCC and PAAS (Table 1), reflecting that the Brahmaputra sediments were derived largely from crustal felsic sources. Moreover, the Al2O3/TiO2 ratio, which can be used to infer mafic, intermediate and felsic rock compositions (see Keskin [40] and references therein) varied from 10 to 34 and according to Hayashi et al [41] the Al2O3/TiO2 ratios in mafic rock types range from ~3 to 8, intermediate types from ~8 to 21, and felsic types from ~21 to 70. The high Al2O3/TiO2 values in the Brahmaputra sediments (average of ~8) combined with high SiO2 contents (up to 76 wt.%) indicate derivation from mostly intermediate to felsic rock sources.…”
Section: Major Elementsmentioning
confidence: 99%
“…The ratio of SiO 2 /Al 2 O 3 (5.7-7.4) of the studied sediments was higher than the equivalent ratio for both UCC and PAAS (Table 1), reflecting that the Brahmaputra sediments were derived largely from crustal felsic sources. Moreover, the Al 2 O 3 /TiO 2 ratio, which can be used to infer mafic, intermediate and felsic rock compositions (see Keskin [40] and references therein) varied from 10 to 34 and according to Hayashi et al [41] [42] shown in Figure 7. Although scattered, indicating multiple source rocks including basic components, in general the Brahmaputra sediments have K/Rb ratios that plot predominantly within the field that indicate they represent the erosional products of a series of magmatic rocks that could be generated by mixing typical upper continental crustal materials (granodioritic/granitic) with moderate portions of more intermediate/basic compositions.…”
Section: Major Elementsmentioning
confidence: 99%
“…Geochemical data and associated plots are very significant for relevant provenance demarcation (Keskin 2011). The abundance of Cr, Ni, Sc, and Th in clastic sediments can be considered a proxy in provenance studies.…”
Section: Provenancementioning
confidence: 99%
“…Na 2 O/ K 2 O (3,03) sedimanların olgunlaşma derecesinin yüksek olduğuna işaret etmektedir (Pettijohn vd., 1972;Roser ve Korsch, 1986;Fedo vd., 1995;Paikaray vd., 2008). P 2 O 5 (%0,11) değerlerinin, UCC (%0,17) ve PAAS (%0,16) değerlerinden düşük olması apatit ve diğer aksesuar minerallerinin sedimanlar içerisinde az bulunmasından kaynaklanmış olmalıdır (Condie, 1993 (Keskin, 2011;Hossain, vd., 2014 Taylor and McLennan,1985 Pettijhon et al, 1972).…”
Section: Marshall Stabilite Ve Akma Deneyi Bulgularıunclassified